Practical Aspects of a Plea Agreement (bargaining) - Bokhashvili, Irine (Journal of Law, 2023)
In the modern world of negotiations, it is increasingly important to talk about the perfection and renewal of a plea agreement as a speedy justice in the criminal process. The purpose of the presented work is to discuss and analyze the main essential features of a plea agreement based on the current legislation, existing domestic judicial practice, approaches of the European Court and the experience of foreign countries (mostly, the USA), which contribute to the enhancement of proposals for legislative or practical improvement due to the relevant conclusions. The paper reviews such topical issues as: the guilty plea as the subject and basis of a plea agreement and the ratio of benefits gained in exchange for it; Participation of parties in a plea agreement and the analysis of their comparison with the concept of a party qualified to take part in the process; A motion to approve a plea agreement as the main formal basis for a mistrial; The place and role of the so-called "plea agreement standard" in the system of proof standards; The exceptional rule provided by Article 55 of the Criminal Code of Georgia and the issue regarding the independence of the judge during the selection/appointment of the type of punishment; Consideration of the motion for approval of a plea agreement and features of the appeal results (current issues of legislation and judicial practice). As a conclusion, at the end of the paper, the author proposes the opinion on the main problematic aspects, and offers the following summary: at the current stage, it could not be appropriate to introduce changes about increasing the competence of the judge to determine the punishment in the first provisions of a plea agreement of the Criminal Procedure Code of Georgia; It is pertinent to develop the interpretation of the legal regulation and judicial practice in the direction of defining only beyond a reasonable doubt standard as a single standard for establishing a guilty verdict.; It is appropriate to refine the legal regulations and establish a new judicial practice of the prosecutor's appeal of the verdict on the approval of a plea agreement, and it is proposed to recommend that such a case should be considered as a revision of the verdict due to newly discovered circumstances and that the prosecutor exercise the mentioned competence on the basis of a motion.